Emocje i funkcje zapachu w "Marcovaldzie" Calvina, w "Księżycu i ogniskach" Pavesego oraz w "Profesorze i syrenie" Lampedusy - Gotowicka, Tamara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
More and more studies indicate scent acts as channel of communication for emotions, that there is communication of emotions through scent. The metaphorical term "feel emotions" can thus be taken literally. The sense of smell plays a significant role in our lives, and in literature because it influences our psychophysical activity. Our ability to smell and feel emotions has its source in the same part of the brain where both memories and feelings are stored. This is because the olfactory brain is part of the brain?s limbic system which is responsible for emotions and memory. The extraordinary power of the smell evokes memories from the distant past which are much more durable than the impressions caused by visual stimuli.
Keywords: emocje; zapach; odczucie; tożsamość; biblioterapia; emotions; odour/scent; feelings; identity; bibliotherapy